Interactive Narration in the Digital Age - Huang Minfen (Bina Nusantara University, 2008)
Interactive narration based on new media has become important research topic for post-narratology. It features non-linearity and can be classified as person-to-person, person-to-machine, and machine-to-machine. In order to fulfil the potential of interactive narration, we have to deal with the contradiction between narration and interaction properly, and lucubrate the motive of interactors and the narrative effects on them.